An exploratory study of the needs of immigrant women offenders - Delic, Svjetlana (University of Ottawa (Canada), 2005)
This study explores the needs of immigrant women in Canadian federal correctional facilities. It specifically examines whether they have any unique needs that stem directly from their immigration status and migration-related hardships. My research included ten in-depth interviews with immigrant women prisoners at the Grand Valley Institution for Women in Ontario and a questionnaire sent to all foreign-born women in Canadian federal correctional institutions (one institution did not have any immigrant offenders at the time). Seven need areas, which were derived from the literature, were explored during the interview: culture-specific programming, migration-related sources of stress, problems with seeking psychological help, parenting issues, vocational skills, language skills, and immigration-related concerns. Considering that existing literature does not specifically identify the unique needs of immigrant female offenders, it appeared more appropriate to develop the questionnaire following the analysis of the interviews. Consequently, some additional themes, not identified in the literature on immigrants, emerged during the interviews and were included in the questionnaire. For example, some of the interviewees identified additional concerns, such as not having access to culture-specific foods and products; having strained relationships with their extended families; or feeling that their culture-specific behavior was misread by the correctional staff. I situated my research findings and proposed recommendations within a broader context of Canadian debates on multiculturalism. Immigrant women belong to various ethno-cultural groups and both they and the correctional system are affected by Canadian multicultural practices.
Keywords: Sociology, Criminology and Penology.